QUANTUM CHEMICAL CALCULATION OF STRUCTURAL AND THERMODYNAMIC PROPERTIES OF ETHYL METHYL SULFONE IN THE GAS PHASE (Proceedings of the YSU B: Chemical and Biological Sciences, 2023)
A detailed conformational analysis of ethyl methyl sulfone has been carried out using quantum chemical approaches, by revealing all stable conformers, their energy, structural parameters, relative population, and IR spectra at different levels of theory. Thermochemical parameters, such as energy, entropy and heat capacity of ethyl methyl sulfone stable conformers in the gas phase were calculated directly using the wB97XD/6-311++G(2df, 2pd) density functional theory method. Some correlation has been established between the structural characteristics of various conformers and their thermodynamic properties.
Keywords: ethyl methyl sulfone; density functional theory; thermochemistry